Simultaneous Analysis of Ammonium and Nitrate Ions Levels with Potentiometric Multi-commutation Flow System Method - Hikmah, Fajrin Nurul; Mulyono, Tri; Zulfikar, Zulfikar (Jurnal ILMU DASAR, 2021)
This study aims to develop a multi-commutation flow system method for simultaneous determination of ammonium ion and nitrate ion using two detectors, namely ammonium ion selective electrode and nitrate ion selective electrode. The multi-commutation flow system method uses two three way selenoide valves to adjust the sample flow and ISA solution. The selenoid valve alternately flows the sample and ISA solution to the ion selective electrode. Flow control by three way selenoid valves is controlled by LabView which is programmed in the computer. The computer is connected with Arduino and a relay that functions as an on-off switch on the three way valve selenoid. This method is then applied to measure the levels of ammonium ions and nitrate ions in well water samples. The performance of the multi-commutation flow system determined includes linearity, limit detection, sensitivity, repeatability, and recovery test. Ammonium analysis results show good performance with several criteria. Ammonium linearity value is 0,9991, ammonium detection limit value is 2,23 × 10-5 M, sensitivity of ion selective electrode ammonium is 45,39 mV per decade, the repeability value is less than 2% and the recovery percentage of ammonium is 115%. While the results of the nitrate analysis showed a linearity value of 0,9937, a nitrate detection limit value of 1,31 × 10-5 M, sensitivity of the ion selective electrode nitrate of -110,58 mV per decade, a repeatability value of less than 2% and a recovery percentage of 87% nitrate. Keywords: Flow Analysis, multi-commutation, ammonium, nitrat, simultaneous.